Electro-optical properties of Er-doped SnO2 thin films - Morais, E. A.; Scalvi, LVA; Geraldo, V; Scalvi, RMF; Ribeiro, SJL; Santilli, C. V.; Pulcinelli, S. H. (Elsevier B.V., 2004)
Photoconductivity of SnO2 sol-gel films is excited, at low temperature, by using a 266 nm line-fourth harmonic-of a Nd:YAG laser. This line has above bandgap energy and promotes generation of electron-hole pairs, which recombines with oxygen adsorbed at grain boundary. The conductivity increases up to 40 times. After removing the illumination on an undoped SnO2 film, the conductivity remains unchanged, as long as the temperature is kept constant. Adsorbed oxygen ions recombine with photogenerated holes and are continuously evacuated from the system, leaving a net concentration of free electrons into the material, responsible for the increase in the conductivity. For Er doped SnO2, the excitation of conductivity by the laser line has similar behavior, however after removing illumination, the conductivity decreases with exponential-like decay. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: erbium doping; oxygen adsorption; photoconductivity; tin dioxide films